Georgie, all along [large type] - Clayborn, Kate (Thorndike Press Large Print softcover romance and women's fiction., 2023)
"Longtime personal assistant Georgie Mulcahy has made a career out of putting others before herself. When an unexpected upheaval sends her away from her hectic job in L.A. and back to her hometown, Georgie must confront an uncomfortable truth: her own wants and needs have always been a disconcertingly blank page. But then Georgie comes across a forgotten artifact--a "friendfic" diary she wrote as a teenager, filled with possibilities she once imagined. To an overwhelmed Georgie, the diary's simple, small-scale ideas are a lifeline--a guidebook for getting started on a new path. Georgie's plans hit a snag when she comes face to face with an unexpected roommate--Levi Fanning, onetime town troublemaker and current town hermit. But this quiet, grouchy man is more than just his reputation, and he offers to help Georgie with her quest. As the two make their way through her wishlist, Georgie begins to realize that what she truly wants might not be in the pages of her diary after all, but right by her side--if only they can both find a way to let go of the pasts that hold them back"--